EPE photovoltaic adhesive film and preparation method thereof

By using high branching POE resin and high transparency styrene-methyl methacrylate copolymer in EPE photovoltaic film, the problems of separation between EPE film layers, insufficient peel strength and low light transmittance are solved, and stronger peel strength and higher light transmittance are achieved, while improving the aging resistance of the film.

CN119799176APending Publication Date: 2025-04-11ZHEJIANG TRANSFAR SYNTHETIC MATERIAL CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411994583.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing EPE photovoltaic films have problems such as interlayer separation, insufficient peel strength and low light transmittance.

Method used

Using POE resin with high branching and styrene-methyl methacrylate copolymer with high transparency, the cohesion and adhesion properties of the POE layer are improved and the bonding power between layers is enhanced through a three-layer sandwich structure design.

Benefits of technology

The interlayer bonding force of the EPE adhesive film is improved, the peel strength is enhanced, and the high light transmittance is maintained, which improves the aging resistance of the adhesive film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224319560000061
    Figure BDA0005224319560000061
  • Figure BDA0005224319560000091
    Figure BDA0005224319560000091
  • Figure BDA0005224319560000101
    Figure BDA0005224319560000101
Patent Text Reader

Abstract

The invention provides an EPE photovoltaic adhesive film and a preparation method thereof. The POE layer of the EPE photovoltaic adhesive film adopts the POE resin with high branching degree, so that intermolecular entanglement is enhanced, and the peel strength of the adhesive film is improved. And the styrene-methyl methacrylate copolymer is also added into the POE layer, so that the light transmittance and the weather resistance of the adhesive film are improved, the absorption effect of the POE layer on a polar auxiliary agent is improved, interlayer separation is prevented, and the aging resistance is enhanced. Therefore, the EPE adhesive film provided by the invention keeps high light transmittance while improving the peel strength and weather resistance, and solves the problems of interlayer separation, insufficient peel strength and low light transmittance of the existing EPE adhesive film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of encapsulation adhesive films, and in particular relates to an EPE photovoltaic adhesive film and a preparation method thereof. Background Art

[0002] Photovoltaic film is an indispensable packaging material in solar cell modules. Its main function is to bond the cell to the upper glass and the lower backplane or glass, while protecting the cell from external environmental influences such as moisture, oxygen, etc., to ensure the long-term stability and reliability of the cell module. Photovoltaic film must have good key properties such as light transmittance, adhesion, aging resistance and water vapor permeability resistance. Generally speaking, the photovoltaic encapsulation film is required to have a bonding strength of more than 40N / cm with the glass and backplane after PCT 48 h aging.

[0003] The main types of photovoltaic films on the market include EVA film, POE film and EPE three-layer co-extruded film. EVA film is widely used due to its high light transmittance and excellent bonding performance, but it has problems such as high water vapor permeability, poor anti-aging performance and easy occurrence of PID (potential induced decay). POE film is known for its low water vapor permeability and high volume resistivity. Its anti-PID performance is better than EVA, but its light transmittance is low and it is prone to slippage during the lamination process. EPE film combines the advantages of EVA and POE. Its specific structure is EVA-POE-EVA. Through the three-layer structure design, the middle layer POE provides the advantages of anti-PID and low water vapor permeability, and the outer layer EVA provides good adhesion.

[0004] However, EVA is a polar material, while POE is a non-polar material without carbon-oxygen bonds. The polarity difference between the two is large, so the polar additive in the POE layer will continue to migrate to the EVA layer, causing changes in the internal structural properties of the film, reducing the interlayer bonding force between POE and EVA, and thus causing the occurrence of interlayer separation. In this regard, patent CN 117801691 A discloses an anti-precipitation EPE co-extruded packaging film, which adds a modified cross-linking agent with a polyurethane structure and a modified silane coupling agent with an adamantyl structure to the POE layer, so that the polarity of the POE layer is improved, the mobility of the additive as a whole is reduced, and the role of blocking electron migration is blocked, but the obtained EPE film has low peeling force and poor light transmission filtration. Patent CN 115926667 A discloses an EPE type three-layer co-extruded film, which enhances the interlayer bonding force by adding polar resin to the POE layer and the EVA layer to solve the problem of interlayer separation. However, the addition of polar resin ethylene-butyl acrylate copolymer or bisphenol A epoxy vinyl ester resin will reduce the light transmittance of the EPE film, and the peeling force of the EPE film is not clear.

[0005] Therefore, it is necessary to develop a new type of EPE film that can prevent interlayer separation so that it can have stronger peel strength while maintaining high light transmittance. Summary of the invention

[0006] In order to solve the problems of interlayer separation, insufficient peel strength and low light transmittance of EPE films in the prior art, the present invention provides a new EPE photovoltaic film, which not only solves the problem of interlayer separation, but also has excellent peel strength and can improve light transmittance.

[0007] The technical solution adopted by the present invention is: an EPE photovoltaic adhesive film, including a three-layer sandwich structure, wherein the three-layer sandwich structure includes an EVA layer, a POE layer, and an EVA layer which are stacked in sequence; the POE layer includes the following preparation raw materials in parts by weight: 100 parts of POE resin, 5-15 parts of styrene-methyl methacrylate copolymer, 0.1-0.5 parts of a compatibilizer, and 0.35-14 parts of an auxiliary agent; the POE resin has a weight average molecular weight of 20000-600000 g / mol, a degree of branching of 40-180 / 1000C, and a melt index of 1-20 g / 10 min at 190°C and a load of 2.16 kg.

[0008] POE resin with high branching degree has more long chain side chains, which can increase the entanglement between molecules, thereby improving the cohesion and bonding performance of the material. POE resin with higher melt index has better fluidity during processing, which helps to increase the contact area with the bonded material, but too high melt index may cause the resin to flow too much, making it difficult to form a uniform bonding layer on the surface of the bonded material. Therefore, the present invention preferably uses POE resin with higher branching degree and suitable melt index as the raw material of the POE layer of the EPE film, which can further improve the peel strength of the EPE film while facilitating processing. However, higher branching degree will reduce the transparency of POE resin, because the increase of side chains may cause more intermolecular scattering. Therefore, the present invention also adds an appropriate amount of styrene-methyl methacrylate copolymer with high transparency and high weather resistance in the POE layer. Styrene-methyl methacrylate copolymer can have good compatibility with POE resin under the action of compatibilizer. Moreover, the methyl methacrylate unit in the styrene-methyl methacrylate copolymer has a strong polarity, which can not only increase the compatibility with the EVA layer and thus enhance the bonding force between the layers, but also improve the absorption effect of the POE layer on the polar additive, and prevent the polar additive from migrating and precipitating to the EVA layer and causing changes in the internal structural properties of the film. It is also very beneficial to solve the delamination problem of the EPE film, so that the EPE film also has excellent aging resistance.

[0009] Preferably, the POE resin has a weight average molecular weight of 50,000-500,000 g / mol, a branching degree of 55-120 / 1000C, and a melt index of 1-15 g / 10 min at 190°C and a load of 2.16 kg.

[0010] Preferably, the POE resin is one or more combinations of branched structural materials prepared by solution polymerization using ethylene or ethylene and C3-C5 olefins as raw materials. In the present invention, the branched structural material can be prepared by the following method:

[0011] Add an organic solvent and a catalyst into a reactor, control the temperature at 10-100°C, introduce ethylene into the reactor to carry out a polymerization reaction, the ethylene pressure is 0.1-5MPa, and the reaction time is 10-90min. After the reaction is completed, the reaction solution is added to acidified ethanol to terminate the reaction to obtain a solid precipitate. After washing and drying the solid precipitate, a branched polyolefin material is obtained.

[0012] The polymerization reaction is carried out in an organic solvent, which is one or more of dichloromethane, toluene and n-hexane. Preferably, the polymerization reaction temperature is 20-80° C. and the reaction pressure is 0.5-3 MPa.

[0013] The catalyst is a late transition metal catalyst. The late transition metal catalyst is a metal complex olefin polymerization catalyst with late transition metal atoms such as nickel (II), palladium (II), iron (II), cobalt (II), ruthenium (II) as the active center, and the chelated ligand is selected from types such as N^N, P^N, N^O, P^O. All kinds of late transition metal catalysts that can catalyze ethylene polymerization to prepare branched polyolefins and can obtain the defined parameters of the branched polyolefin material of the present invention are applicable to the present invention. In the present invention, a branched structure with adjustable long and short branched chain structures is obtained by long-chain branching polymerization in a solution using a late transition metal catalyst. Since the present invention is ethylene in-situ polymerization, the branched chain contains long chains and short chains, has a high degree of branching, and the long branches are used to increase the crosslinking points, so the crystallinity is low, and the elastomer properties are improved.

[0014] Further, the late transition metal catalyst is a Brookhart catalyst; such as (a-diimine) nickel / palladium complex; more preferably an α-diimine nickel catalyst. When the catalyst is an α-diimine nickel catalyst, a co-catalyst is also added, and the co-catalyst is one or more of diethylaluminum monochloride, ethylaluminum dichloride, methylaluminoxane, polymethylaluminoxane, sesquiethylaluminum chloride (EASC), preferably sesquiethylaluminum chloride. The molar ratio of Al in the co-catalyst to Ni in the α-diimine nickel catalyst is 50-1000:1.

[0015] Preferably, the POE resin is an ethylene-octene copolymer elastomer obtained by in-situ polymerization of ethylene and 1-octene, wherein the insertion rate of 1-octene is 10 mol%-30 mol%.

[0016] Preferably, the POE resin is an ethylene-butene copolymer elastomer obtained by in-situ polymerization of ethylene and 1-butene, wherein the insertion rate of 1-butene is 10 mol%-45 mol%.

[0017] Preferably, the POE resin is a branched polyolefin elastomer with a long and short branched chain structure obtained by solution polymerization using ethylene as a single raw material, and the proportion of alkyl groups with a length of C6 or above in the side chain of the branched polyolefin elastomer is greater than 10%. More preferably, the branching degree of the branched polyolefin elastomer is 60-120 / 1000C, and the melt index at 190°C and a load of 2.16kg is 5-15g / 10min.

[0018] Preferably, the thickness of the POE layer in the three-layer sandwich structure is 100-300 μm.

[0019] Preferably, the density of the POE resin is 0.85-0.88 g / cm 3 .

[0020] Preferably, the raw materials for preparing the POE layer include 7-13 parts of styrene-methyl methacrylate copolymer.

[0021] Preferably, the raw materials for preparing the POE layer include 0.3-0.5 parts of a compatibilizer.

[0022] Preferably, the compatibilizer is selected from POE grafted maleic anhydride and / or POE grafted glycidyl methacrylate.

[0023] Preferably, the auxiliary agent includes at least one of a cross-linking agent, a co-cross-linking agent, an antioxidant, a light stabilizer, and a UV absorber.

[0024] Preferably, the POE layer further comprises the following raw materials in parts by weight: 0.1-3 parts of a cross-linking agent, 0.1-5 parts of a co-cross-linking agent, 0.05-2 parts of an antioxidant, 0.05-2 parts of a light stabilizer, and 0.05-2 parts of a UV absorber.

[0025] Preferably, the EVA layer comprises the following raw materials in parts by weight: 100 parts of EVA resin, 0.1-5 parts of co-crosslinking agent, 0.1-3 parts of crosslinking agent, 0.05-2 parts of antioxidant, 0.05-2 parts of light stabilizer, and 0.2-0.6 parts of silane coupling agent.

[0026] Preferably, the auxiliary crosslinking agent in the POE layer and the auxiliary crosslinking agent in the EVA layer are both selected from at least one of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triethyl acrylate, acrylamide, divinylbenzene, diisocyanate or methylenebisacrylamide.

[0027] Preferably, the crosslinking agent in the POE layer and the crosslinking agent in the EVA layer are selected from at least one of benzoyl oxide, lauroyl peroxide, di-tert-butyl peroxide, diisopropyl peroxide, dicumyl peroxide, tert-butyl perbenzoate, tert-butyl peroxyvalerate, tert-butyl peroxy-2-ethylhexyl carbonate, diisopropyl peroxydicarbonate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide or tert-butyl hydroperoxide.

[0028] Preferably, the antioxidant in the POE layer and the antioxidant in the EVA layer are selected from at least one of butylated hydroxytoluene, 2,4-di(dodecylthiomethyl)-6-methylphenol, dilaurylthiodipropionate, 1,3,5-tri(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris(2,4-di-tert-butylphenyl) phosphite.

[0029] Preferably, the light stabilizer in the POE layer and the light stabilizer in the EVA layer are selected from bis-2,2,6,6-tetramethylpiperidinol sebacate and / or bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0030] Preferably, the ultraviolet absorber in the POE layer is selected from at least one of 2-hydroxy-4-n-octyloxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2,4-dihydroxybenzophenone, 2-(2-hydroxy-3,5-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine-2-yl)-5-octyloxyphenol and 3,5-di-tert-butyl-4-hydroxybenzoic acid hexadecyl.

[0031] Preferably, the silane coupling agent in the EVA layer is selected from at least one of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, vinyltri-tert-butoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, methacryloxy oligomer, and γ-methacryloxypropyltrimethoxysilane.

[0032] The present invention also provides a method for preparing the EPE photovoltaic adhesive film, comprising: melt-blending the raw materials for preparing the EVA layer and the POE layer according to the formula, and then co-extruding and casting the raw materials into films to obtain the photovoltaic adhesive film with a three-layer sandwich structure.

[0033] Preferably, the preparation method comprises:

[0034] S1: According to the formula, the POE layer and EVA layer raw materials are added to a mixer and mixed to obtain a POE layer mixed raw material and an EVA layer mixed raw material;

[0035] S2: placing the mixed raw materials of the POE layer and the mixed raw materials of the EVA layer in a twin-screw extruder for melt blending, and then simultaneously discharging, pulling, compounding, and stretching through the co-extrusion cast film die heads of several twin-screw extruders to prepare a composite film with a layered structure;

[0036] S3: The composite film is subjected to thickness measurement, edge pressing, shaping, edge trimming and rolling to obtain the EPE photovoltaic film.

[0037] Beneficial effects of the present invention:

[0038] (1) The use of high-branched POE resin with more long-chain branches increases the entanglement between molecules, thereby improving the cohesion and adhesion of the material, and thus improving the peel strength of the EPE film;

[0039] (2) Adding styrene-methyl methacrylate copolymer with high transparency and high weather resistance to the POE layer enables the EPE film to have stronger peel strength while maintaining high light transmittance;

[0040] (3) The addition of styrene-methyl methacrylate copolymer can not only increase the compatibility of the POE layer and the EVA layer, thereby enhancing the bonding force between the layers, but also improve the absorption effect of the POE layer on the polar additive, preventing the change of the internal structural properties of the film caused by the migration and precipitation of the polar additive to the EVA layer. It is also very beneficial to solve the delamination problem of the EPE film, so that the EPE film also has excellent aging resistance. DETAILED DESCRIPTION

[0041] The following describes the embodiments of the present invention through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0042] Unless otherwise specified, the methods used in the examples of the present invention are all conventional methods, and the reagents used are all commercially available.

[0043] Preparation example:

[0044] α-Diimine nickel catalyst (2 μmol) and sesquiethylaluminum chloride (2 mmol, Al:Ni molar ratio = 1000) were added to 100 mL of n-hexane solvent, the temperature was controlled at 20-80°C, ethylene was introduced to carry out polymerization reaction, timing was started after the ethylene pressure was stable, the ethylene pressure was 0.1-5 MPa, the reaction time was 10-70 min, after the reaction was completed, the reaction solution was added to 200 mL of acidified ethanol, stirred for 10 h, filtered, washed with ethanol, and vacuum dried to obtain a branched polyolefin material.

[0045] The α-diimine nickel catalyst used in this embodiment is prepared according to the following reaction formula:

[0046]

[0047] In the formula I, R1 is phenyl or substituted phenyl, and the substituted phenyl is p-aminophenyl, p-methylphenyl, p-methoxyphenyl or p-tert-butylphenyl; R2 is phenyl or substituted phenyl, and the substituted phenyl is p-methylphenyl, p-methoxyphenyl, p-fluorophenyl or p-tert-butylphenyl; R3 is phenyl or substituted phenyl, and the substituted phenyl is p-methoxyphenyl, p-fluorophenyl or p-tert-butylphenyl.

[0048] In a toluene solvent, the aniline compound represented by formula II and diacetyl are mixed in a molar ratio of 2-2.2:1, and heated to 60-90°C for reaction for 20-24 hours under the action of a catalytic amount of p-toluenesulfonic acid. Then, the mixture is separated by water using a water separator and refluxed for 2-3 days to obtain a diimine ligand compound represented by formula III.

[0049] The diimine ligand compound shown in formula III and (DME)NiBr2 are mixed in a molar ratio of 1:0.5-2, dissolved in dichloroethane solvent, and stirred for reaction for 10-24 hours under nitrogen protection to obtain the α-diimine nickel catalyst shown in formula I.

[0050] In this embodiment, the α-diimine nickel catalyst in which R1, R2 and R3 are all p-tert-butylphenyl is prepared by the following specific method:

[0051] 2,4-di(p-tert-butylphenyl)-6-di-p-tert-butylphenyl methylaniline (4mmol) and diacetyl (2mmol) were dissolved in 100mL toluene, and 10mg of p-toluenesulfonic acid (PTSA) was added, and the mixture was stirred and refluxed at 80°C for 24h. Then, the mixture was refluxed for 3 days using a Dean□stark water separator. After the reaction solution was cooled to room temperature, part of the solvent was evaporated under reduced pressure to precipitate a solid. 400mL of methanol was added to precipitate a solid product, which was filtered, and the filter cake was washed with methanol and dried to obtain a diimine ligand compound with a yield of 81%.

[0052] Under nitrogen protection, the diimine ligand compound and (DME)NiBr2 (0.2 mmol) and the diimine ligand compound (0.20 mmol) were mixed and dissolved in 5 mL of dichloromethane, and the reaction was stirred at room temperature for 20 hours. After the dichloromethane was removed under reduced pressure, ether was added to precipitate a red solid, which was filtered, washed with ether, and dried to obtain an α-diimine nickel catalyst with a yield of about 85%.

[0053] Using ethylene as raw material, n-hexane as solvent, α-diimine nickel catalyst as catalyst, sesquiethylaluminum chloride as co-catalyst, by adjusting the ratio of main catalyst and co-catalyst, process and product compound combination, POE resins B1 to B3 were prepared respectively:

[0054] POE resin B1: The proportion of alkyl groups with a length of C6 or above in the side chain is 15%, the melt index is 7g / 10min, the molecular weight is 180,000 g / mol, and the branching degree is 65 / 1000C;

[0055] POE resin B2: The proportion of alkyl groups with a length of C6 or above in the side chain is 17%, the melt index is 5g / 10min, the molecular weight is 150,000 g / mol, and the branching degree is 75 / 1000C;

[0056] POE resin B3: The proportion of alkyl groups with a length of C6 or above in the side chain is 21%, the melt index is 14g / 10min, the molecular weight is 320,000, and the degree of branching is 118 / 1000C.

[0057] POE resins B4 to B5 are prepared using ethylene, 1-octene or 1-butene as raw materials, alkanes as solvents, and transition metal complexes as catalysts:

[0058] POE resin B4: ethylene-butene copolymer elastomer, in which the insertion rate of 1-butene is 13%, the melt index is 6g / 10min, the molecular weight is 190,000 g / mol, and the branching degree is 68 / 1000C;

[0059] POE resin B5: ethylene-octene copolymer elastomer, in which the insertion rate of 1-octene is 12%, the melt index is 6 g / 10min, the molecular weight is 200,000 g / mol, and the branching degree is 63 / 1000C.

[0060] Embodiment 1:

[0061] An EPE film has a three-layer sandwich structure, comprising an EVA layer, a POE layer and an EVA layer stacked in sequence; wherein the thickness of the EVA layer is 100 μm, and the thickness of the POE layer is 150 μm.

[0062] The EVA layer includes the following raw materials in parts by mass: 100 parts of EVA resin, 0.5 parts of triallyl isocyanurate, 0.4 parts of tert-butyl peroxy-2-ethylhexyl carbonate, 0.3 parts of 3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 0.1 parts of bis(2.2.6.6-tetramethyl-4-piperidinyl) sebacate, and 0.4 parts of vinyltrimethoxysilane.

[0063] The POE layer includes the following raw materials in parts by mass: 100 parts of POE resin (POE resin B1 is used in experiment 1-1, POE resin B2 is used in experiment 1-2, POE resin B3 is used in experiment 1-3, POE resin B4 is used in experiment 1-4, and POE resin B5 is used in experiment 1-5), 5 parts of styrene-methyl methacrylate copolymer, 0.5 parts of POE grafted maleic anhydride, 0.6 parts of tert-butyl perbenzoate, 0.4 parts of trimethylolpropane triethyl acrylate, 0.2 parts of 1,3.5-tris(4-tert-butyl-3-hydroxy-2.6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 0.1 parts of bis(2.2.6.6-tetramethyl-4-piperidinyl) sebacate, and 0.1 parts of 2-hydroxy-4-n-octyloxybenzophenone.

[0064] The preparation method of the EPE film comprises:

[0065] S1: According to the formula, the POE layer and EVA layer raw materials are added to a mixer and mixed respectively, and mixed and stirred at a temperature of 40° C. and a speed of 80 rpm for 2 hours to obtain a POE layer mixed raw material and an EVA layer mixed raw material respectively;

[0066] S2: placing the mixed raw materials of the POE layer in a twin-screw extruder, and melt blending them at temperatures of 90°C, 95°C, and 105°C, and a rotation speed of 50 rpm; placing the mixed raw materials of the EVA layer in a twin-screw extruder, and melt blending them at temperatures of 80°C, 90°C, and 100°C, and a rotation speed of 50 rpm; and then simultaneously discharging, pulling, compounding, and stretching the co-extrusion cast film die heads of the three twin-screw extruders to prepare a composite film with a layered structure;

[0067] S3: The composite film is subjected to thickness measurement, edge pressing, shaping, edge trimming and rolling to obtain the EPE photovoltaic film.

[0068] Embodiment 2:

[0069] An EPE film, whose layered structure is the same as that of Example 1.

[0070] The raw materials for preparing the EVA layer are the same as those in Example 1.

[0071] The POE layer includes the following raw materials in parts by mass: 100 parts of POE resin B2, 0-20 parts of styrene-methyl methacrylate copolymer (no addition in comparative experiment 2-1, 7 parts added in experiment 2-1, 10 parts added in experiment 2-2, 13 parts added in experiment 2-3, 15 parts added in experiment 2-4, and 20 parts added in comparative experiment 2-2), 0.5 parts of POE grafted maleic anhydride, 0.6 parts of tert-butyl perbenzoate, 0.4 parts of trimethylolpropane triethyl acrylate, 0.2 parts of 1,3.5-tris(4-tert-butyl-3-hydroxy-2.6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 0.1 parts of bis(2.2.6.6-tetramethyl-4-piperidinyl) sebacate, and 0.1 parts of 2-hydroxy-4-n-octyloxybenzophenone.

[0072] The preparation method of the EPE photovoltaic adhesive film provided in Example 2 is the same as that in Example 1.

[0073] Embodiment 3:

[0074] An EPE film, whose layered structure is the same as that of Example 1.

[0075] The raw materials for preparing the EVA layer are the same as those in Example 1.

[0076] The POE layer includes the following raw materials in parts by mass: 100 parts of POE resin B2, 10 parts of styrene-methyl methacrylate copolymer, 0-1 parts of POE grafted maleic anhydride (no addition in comparative experiment 3-1, 0.1 parts added in experiment 3-1, and 0.3 parts added in experiment 3-2), 0.6 parts of tert-butyl perbenzoate, 0.4 parts of trimethylolpropane triethyl acrylate, 0.2 parts of 1,3.5-tris(4-tert-butyl-3-hydroxy-2.6-dimethylphenyl)-1,3,5-triazine-2,4,6-(1H,3H,5H)-trione, 0.1 parts of bis(2.2.6.6-tetramethyl-4-piperidinyl) sebacate, and 0.1 parts of 2-hydroxy-4-n-octyloxybenzophenone.

[0077] The preparation method of the EPE photovoltaic adhesive film provided in Example 3 is the same as that in Example 1.

[0078]

Performance test

[0079] The EPE photovoltaic adhesive films prepared in Examples 1-3 of the present invention were subjected to relevant performance tests, and the test results are shown in Table 1.

[0080] The test method is as follows:

[0081] (1) Light transmittance: Tested according to the method described in GB / T 29848-2013 “Ethylene-vinyl acetate copolymer (EVA) adhesive film for photovoltaic module encapsulation”.

[0082] (2) Cross-linking degree: After the film undergoes cross-linking reaction, the degree of cross-linking is determined by xylene extraction. Cut the film into 1 mm pieces, weigh them as m0, and place them in a stainless steel mesh bag. Immerse them in boiling xylene and extract them for 4 hours. The uncross-linked film will be extracted into the xylene, and the remaining undissolved film is the cross-linked film m1.

[0083] Crosslinking degree = crosslinked film m1 / total film weight m0×100%

[0084] (3) Peel force test: The initial peel force and PCT48 peel force between the glass and the film were tested according to the method described in GB / T 29848-2013 “Ethylene-vinyl acetate copolymer (EVA) film for photovoltaic module encapsulation”.

[0085] (4) Hygrothermal aging performance: The EPE film was subjected to a hygrothermal aging test. Conditions: Test conditions: +85°C, relative humidity 85%, test time 1000 hours. Delamination was visually observed to determine the performance.

[0086] (5) Precipitation test: Take a 5g EPE film sample that has been delaminated after wet heat aging, wipe the interface between the layers with a dust-free cloth, clean it, and then weigh it. Calculate the lost mass, which is the precipitation amount of the film additive.

[0087] (6) UV aging: The obtained EPE film was subjected to UV irradiation aging test according to the requirements of the International Electrotechnical Commission standard IEC61345. Test conditions: the surface temperature of the test piece is 60±5℃, the UV wavelength range is 280-400nm, the irradiation intensity is 60kW·h / m2, and the UV irradiation test time is 2000hr. The yellowing index (ΔYI) before and after the test was measured according to HG / T3862-2006.

[0088] Table 1. Test results

[0089]

[0090]

[0091] According to Table 1, in Example 1, branched polyolefin elastomers (POE resins B1 to B3) prepared from single ethylene as raw materials were used in experiments 1-1 to 1-3, and the peel strength of the obtained EPE film was significantly improved with the increase of the branching degree of the branched polyolefin elastomer. Experiments 1-5 and 1-4 respectively used ethylene-butene copolymers (POE resin B4) and ethylene-octene copolymers (POE resin B5) with a branching degree close to POE resin B1. The EPE film prepared by ethylene-octene copolymer in experiment 1-5 was superior to the EPE film prepared by ethylene-butene copolymer in experiment 1-4 in terms of mechanical properties. This may be because octene has a long chain, which increases the entanglement between molecules, improves the cohesion and bonding properties of the material, and thus enhances the overall peel strength of the EPE film, but it is still not as good as experiment 1-1. In addition, when preparing photovoltaic adhesive films, POE resins with a melt index of 5-15g / 10min are generally selected. If the melt index is too low, processing and cross-linking are difficult, and if the melt index is too high, the mechanical properties are poor and the compatibility with other indicators is not good. However, for ethylene-butene copolymer or ethylene-octene copolymer POE resins, when the molecular weight and branching degree are constant, the adjustment space of the melt index is very small, so it is limited in the application of photovoltaic adhesive films. However, when a branched polyolefin elastomer with a long and short branched chain structure prepared by a solution polymerization method using a single ethylene as a raw material is used as a POE resin (such as POE resins B1 to B3), there is a huge difference between the branching types, which makes the adjustment space of the melt index larger. Therefore, experiments 1-1 to 1-3 can improve the initial peel strength of the EPE film without using octene raw materials, by increasing the branching degree of the branched polyolefin elastomer (branching degree 60-120 / 1000C) and adjusting the branch insertion, and have a suitable melt index for processing. However, the increase of long chain branches in branched polyolefin elastomers may also lead to more intermolecular scattering, thereby reducing the transparency of POE resin. As the degree of branching increases, the amount of additive precipitation tends to increase, and the PCT48 peel force also tends to decrease. The reason may be that the amount of styrene-methyl methacrylate copolymer in the POE layer raw material has not been adaptively adjusted with the increase of the degree of branching.

[0092] Therefore, Example 2 explores the amount of styrene-methyl methacrylate copolymer in the POE layer raw material based on Experiment 1-2, i.e., POE resin B2. Combined with Experiments 1-2 in Example 1 and each experiment in Example 2, it can be seen that compared with Comparative Experiment 2A, the addition of high-transparency styrene-methyl methacrylate copolymer can not only effectively improve the light transmittance of the EPE film, but also enhance the cross-linking density and reduce the amount of additive precipitation of the POE layer, thereby effectively solving the problem of separation between the film layers and improving the wet heat aging performance of the EPE film. The reason is that the methyl methacrylate unit in the styrene-methyl methacrylate copolymer has a strong polarity, which can not only increase the compatibility with the EVA layer to enhance the bonding force between the layers, but also improve the absorption effect of the POE layer on the polar additive, prevent the change of the internal structural properties of the film caused by the migration and precipitation of the polar additive to the EVA layer, and is also very beneficial to solving the delamination problem of the EPE film, so that the EPE film also has excellent aging resistance. However, according to comparative experiment 2B and experiments 2-1 to 2-4, as the amount of styrene-methyl methacrylate copolymer added increased, the light transmittance of the EPE film finally stabilized at around 93%, but the peel strength of the EPE film showed a trend of first increasing and then decreasing, and after excessive addition of styrene-methyl methacrylate copolymer, the PCT48 peel strength of the EPE film in comparative experiment 2B was less than 40 / Ncm -1 Therefore, the addition amount of styrene-methyl methacrylate copolymer in the raw material for preparing the POE layer is preferably 7-13 parts.

[0093] Example 3 explores the amount of compatibilizer in the raw material of the POE layer based on Experiment 2-2. Combined with comparative experiment 3A, it can be seen that the addition of compatibilizer can effectively improve the compatibility of styrene-methyl methacrylate copolymer and POE resin, so that styrene-methyl methacrylate copolymer can be evenly dispersed in the POE layer, which helps to exert the effect of styrene-methyl methacrylate copolymer. However, with the further increase in the amount of compatibilizer, the peel strength of the prepared EPE film is not significantly improved. Therefore, the amount of compatibilizer added in the raw material for the preparation of the POE layer is preferably 0.3-0.5 parts.

[0094] The embodiments described above are merely descriptions of preferred implementations of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope of the present invention.

Claims

1. An EPE photovoltaic film, characterized in that: It comprises a three-layer sandwich structure, wherein the three-layer sandwich structure comprises an EVA layer, a POE layer, and an EVA layer stacked in sequence; The POE layer comprises the following raw materials in parts by weight: 100 parts of POE resin, 5-15 parts of styrene-methyl methacrylate copolymer, 0.1-0.5 parts of compatibilizer, and 0.35-14 parts of auxiliary agent; The POE resin has a weight average molecular weight of 20,000-600,000 g / mol, a branching degree of 40-180 / 1000C, and a melt index of 1-20 g / 10 min at 190° C. and a load of 2.16 kg.

2. The EPE photovoltaic film according to claim 1, characterized in that: The POE resin is one or more combinations of branched structure materials prepared by solution polymerization using ethylene or ethylene and C3-C5 olefins as raw materials.

3. The EPE photovoltaic film according to claim 1, characterized in that: The POE resin is an ethylene-octene copolymer elastomer obtained by in-situ polymerization of ethylene and 1-octene, wherein the insertion rate of 1-octene is 10 mol%-30 mol%.

4. The EPE photovoltaic film according to claim 1, characterized in that: The POE resin is an ethylene-butene copolymer elastomer obtained by in-situ polymerization of ethylene and 1-butene, wherein the insertion rate of 1-butene is 10 mol%-45 mol%.

5. The EPE photovoltaic film according to claim 1, characterized in that: The POE resin is a branched polyolefin elastomer with a long and short branched chain structure prepared by solution polymerization using ethylene as a single raw material, and the proportion of alkyl groups with a length of C6 or above in the side chains of the branched polyolefin elastomer is greater than 10%.

6. The EPE photovoltaic adhesive film according to claim 5, characterized in that: The branching degree of the branched polyolefin elastomer is 60-120 / 1000C.

7. The EPE photovoltaic film according to claim 1, characterized in that: The thickness of the POE layer in the three-layer sandwich structure is 100-300 μm.

8. The EPE photovoltaic film according to claim 1, characterized in that: The density of the POE resin is 0.85-0.88 g / cm 3 .

9. The EPE photovoltaic film according to claim 1, characterized in that: The compatibilizer is selected from POE grafted maleic anhydride and / or POE grafted glycidyl methacrylate.

10. The EPE photovoltaic film according to claim 1, characterized in that: The auxiliary agent includes at least one of a cross-linking agent, a co-cross-linking agent, an antioxidant, a light stabilizer, and an ultraviolet absorber.

Citation Information

Patent Citations

  • EPE type three-layer co-extrusion adhesive film as well as preparation method and application thereof

    CN115926667A

  • Anti-precipitation EPE co-extrusion packaging adhesive film

    CN117801691A